2019
DOI: 10.1016/j.intell.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

First publication of subtests in the Stanford-Binet 5, WAIS-IV, WISC-V, and WPPSI-IV

Abstract: In this article we describe the origins of the subtests that appear on the modern Stanford-Binet Intelligence Scales (SB5), Wechsler Preschool and Primary Scale of Intelligence (WPPSI-IV), Wechsler Intelligence Scale for Children (WISC-V), and Wechsler Adult Intelligence Scale (WAIS-IV). We found that the majority of these subtest formats were first created in 1908 or earlier and that only three have been created since 1980. We discuss the implications of this findings, which are that (1) many subtests have le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The Wechsler scales are among the most frequently used intelligence tests (Carr, 2015; Gibbons & Warne, 2019). Since the first versions, the Wechsler scales have been revised several times.…”
Section: Wppsi and Nepsy In The Assessment Of Mono‐ And Bilingual Chi...mentioning
confidence: 99%
“…The Wechsler scales are among the most frequently used intelligence tests (Carr, 2015; Gibbons & Warne, 2019). Since the first versions, the Wechsler scales have been revised several times.…”
Section: Wppsi and Nepsy In The Assessment Of Mono‐ And Bilingual Chi...mentioning
confidence: 99%
“…Good vocabulary knowledge is not only at the core of linguistic skills such as reading, writing, listening and speaking (Mezynski, 1983;Perfetti & Hart, 2002;Cromley & Azevedo, 2007;Binder et al, 2017), it is also a predictor of academic achievement (Seashore, 1948;Treffers-Daller & Milton, 2013) and it is a core element of IQ tests. The first IQ test, published by Binet and Simon (1907), included questions about words (Gibbons & Warne, 2019), and when Terman adapted the test to English, he was quick to notice the usefulness of a vocabulary test. Terman et al (1918) reported that a vocabulary test consisting of 100 words randomly selected from a dictionary of 18,000 words correlated r ≈ .9 with performance on the Stanford-Binet IQ test in school children from grade 1 to the first year of high school (participants had to explain the meaning of the words).…”
mentioning
confidence: 99%
“…The items on the ICAR test are typical for written intelligence tests. All item types have appeared on intelligence tests for at least 50 years and are well established methods for measuring intelligence in examinees [ 79 ].…”
Section: Methodsmentioning
confidence: 99%